Free fatty acid formation in oil palm fruits during storage - Ainul Farhani, Ahmad Nizam; Muthiyah, Kalaiselvan; Mohd Sabri, Mahmud (IOP Publishing Ltd, 2020)
Free fatty acids (FFAs) are derived from the undesired hydrolysis reaction of glycerides with the presence of lipase, and quantified as acid value for crude palm oil (CPO) grading. Since FFA content is directly proportional to time, duration from harvest to sterilization of fruits is not more than a day. This paper reports peculiar trend of FFA formation over time when the analysis of FFA was carried out differently. Analysis results of FFA and glyceride contents by timely picking the fruitlets (R-fruit) from fresh fruit bunch (FFB) were compared with the fruitlets from spikelet (S-fruit) that were initially removed all for 7 days. The results showed that the increment of FFA content of the latter was 10 hour faster. This implies that the fruitlets from spikelet resemble the detached fruits which having higher rate of FFA formation compared to the fruitlets that attached to FFB. By using SigmaPlot, the graphs of R-fruit and Sfruit were best fitted into damped sine, 5 parameter with linear and rational with 4 parameters respectively. Nevertheless, lower R2 value was obtained for the fruitlets from readily-removed spikelet compared to the fruitlets from FFB, indicating that other factors might have also affected the formation of FFA.